(untitled) (Asian Journal of Plant Biology, 2015)
One of the most important preliminary investigations of callus attributes is the growth characteristics. Most often than not, callus growth curve is sigmoidal in characteristics. In this work, we model callus growth from Glycine wightii from published literature to acquire essential growth constants. These growth constants are only able to be precisely extracted from mathematical modelling of the growth curves using numerous readily available primary models for example logistic, Gompertz, Richards, Schnute, Baranyi-Roberts, Von Bertalanffy, Buchanan three-phase and more recently Huang models. Statistical tests such as root-mean-square error (RMSE), adjusted coefficient of determination (R2), bias factor (BF), accuracy factor (AF) and corrected AICc (Akaike Information Criterion) were utilized to find the best model. The best model was modified Gompertz. The growth constants obtained obtained such as lag, Ymax, Î¼max were 3.78 d, 6.07 mg, and 0.318 d-1, respectively, respectively. Growth parameter constants extracted from the modelling exercise will be helpful for additional secondary modelling implicating the consequence of media conditions as well as other factors on the growth of callus from this plant.